Reply to comment by X. X. Zhang et al. on "Three‐dimensional quantification of soil hydraulic properties using X‐ray computed tomography and image‐based modeling". Issue 7 (8th July 2016) - Tracy, Saoirse R.; Daly, Keith R.; Sturrock, Craig J.; Crout, Neil M. J.; Mooney, Sacha J.; Roose, Tiina
Abstract: In response to the comment raised by Zhang et al. (2016, doi: 10.1002/2015WR018432) we explore the differences in average velocity computed using slip and no‐slip boundary conditions at the air water interface. We consider a porous medium in which the air phase acts to impede the movement of water rather than to lubricate it, a case closer to the observed distribution of water in our CT images. We find that, whilst the slip boundary condition may be a more accurate approximation, in cases where the air phase is seen to impede water movement the differences between the two approaches are negligible. Key Points: Discussion on boundary conditions Slip boundary condition may be more appropriate Both choices of boundary conditions are approximate